A systematic review of medication exposure assessment in prospective cohort studies of community dwelling older australians. - Susan G Poole; J Simon Bell; Natali Jokanovic; Carl M Kirkpatrick; Michael J Dooley (PLoS ONE, 2015)
Introduction It is not known to what extent medication use has been comprehensively assessed in prospective cohort studies of older Australians. Understanding the varying methods to assess medication use is necessary to establish comparability and to understand the opportunities for pharmacoepidemiological analysis. The objective of this review was to compare and contrast how medication-related data have been collected in prospective cohorts of community-dwelling older Australians. Methods MEDLINE and EMBASE (1990-2014) were systematically searched to identify prospective cohorts of ≥1000 older participants that commenced recruitment after 1990. The data collection tools used to assess medication use in each cohort were independently examined by two investigators using a structured approach. Results Thirteen eligible cohorts were included. Baseline medication use was assessed in participant self-completed surveys (n = 3), by an investigator inspecting medications brought to a clinic interview (n = 7), and by interviewing participants in their home (n = 3). Five cohorts sought participant consent to access administrative claims data. Six cohorts used multiple methods to assess medication use across one or more study waves. All cohorts assessed medication use at baseline and 12 cohorts in follow-up waves. Twelve cohorts recorded prescription medications by trade or generic name; 12 cohorts recorded medication strength; and 9 recorded the daily medication dose in at least one wave of the cohort. Seven cohorts asked participants about their "current" medication use without providing a definition of "current"; and nine cohorts asked participants to report medication use over recall periods ranging from 1-week to 3-months in at least one wave of the cohort. Sixty-five original publications, that reported the prevalence or outcomes of medication use, in the 13 cohorts were identified (median = 3, range 1-21). Conclusion There has been considerable variability in the assessment of medication use within and between cohorts. This may limit the comparability of medication data collected in these cohorts.